A Shift-Share Analysis Of The Competitiveness Of Three Major Crop Industries In Malaysia - Ishak, Ahmad Zalili (2007)

(untitled)
Agriculture is one of the main sectors in Malaysian economy. Palm oil, rubber and cocoa were the main agriculture industries in 1960’s and 1970’s. Malaysia’s palm oil industry faced a tough competition from Indonesia. The share of Malaysia’s palm oil export declined from 69.9 percent in 1990 to 50.3 percent in 2005. A similar trend is observed in the case of rubber and cocoa. In 1990, the share of Malaysia’s rubber in the world market was 29.6 percent. By 2005, it has declined to 10.6 percent. In 1990/1991, the share of Malaysia’s cocoa export was 8.8 percent and by 2004/2005, it has declined to 0.9 percent. The study examines the competitiveness of three agricultural sectors; palm oil, rubber and cocoa. The Shift-Share Analysis is utilized to estimate the net shift in each industry.The result shows that palm oil has the greatest potential for industrialization in the long-term. On the other hand, the rubber and cocoa industries show positive results for the short-term. The research and development of palm oil in Malaysia has contributed to the growth of the industry. Currently palm oil is one of the major sectors that contributes to the country’s export earning. Malaysia represents 50.3 percent of the world palm oil export in 2005. The study shows that the cocoa industry exhibits future potential for growth. Hence, it is recommended that more production incentives and supports are provided to revitalize this industry.